Monitoring Indicators for Maternal, Newborn and Child Health at Sub Primary Health Care Centers in Baghdad City: An Evaluative Study - hassoon, majid; Abdulwahid, hala (Iraqi National Journal of Nursing Specialties, 2018)
Objectives: The study aims to evaluate the application of monitoring indicators for maternal, newborn andchild health through the evaluation of impact and coverage health indicators and to evaluate the usefulness of theapplication of these indicators at sub primary health care centers in Baghdad City.Methodology: A descriptive comparative design, which is using the evaluation approach, has been steered atSub Primary Health Centers of Baghdad City in order to evaluate the application; impact and coverage, and theusefulness of monitoring indicators for maternal, newborn and child health from December 4th 2017 to April 29th2018. A multistage, "non-probability" convenient, sample is selected for the present study. A total of six SubPrimary Health Centers in Al-Karkh Health Directorate, compared with six Sub Primary Health Centers in AlRussafaHealth Directorate. A questionnaire is adopted from the World Health Organization "health monitoringmaternal, newborn and child health: understanding key progress indicators" and developed for the purpose of thepresent study. Content validity and internal consistency reliability are determined for the study instrumentthroughout a pilot study. Data were collected through the utilization of the study instrument and the structuredinterview technique as means of data collection. Data were analyzed through the application of descriptivestatistical data analysis approach of frequency, percentage, mean, total scores and range and inferential statisticaldata analysis approach that includes t-test.Results: Findings of the study revealed that the maternal, newborn and child health indicators are not perfectlyapplied and experiencing some deficiencies in their application at the sub primary health care centers.Confirmatory data analysis throughout hypothesis testing has revealed that sub primary health care centers areexperiencing almost the same problems relative to the impact, coverage and usefulness of these indicators.Recommendations: The study recommends that the Ministry of Health and Environment Public HealthDirectorate can take serious planning for action in applying these indicators, periodic and systematically drivenmonitoring and evaluating the application of such indicators, and focal personnel can be encouraged toparticipate in training sessions and workshops for the benefits of applying these indicators